Mindfulness, an Important Concept for Organizations: a Book Review Essay on the Work of Ellen Langer - Albert, Stuart (Academy of Management Review, 1990)
The intent of this essay is to review the work of Ellen Langer, principally her work on the psychology of control and the concept of mindfulness and mindlessness, which she has pioneered. Dr. Langer, an experimental social psychologist in the Department of Psychology at Harvard and author of the book Mindfulness, has been working in these areas for more than 15 years, producing a brilliant stream of work that is theoretically provocative and methodologically sophisticated. Because this work is about significant real-world issues, it can have powerful practical applications. The purpose of this review is to bring her work to the attention of management researchers in general and those in the field of organizational behavior specifically. Her work can be divided into two related streams of research, one dealing with the concept of mindfulness versus mindlessness and one dealing with processes of control. This review begins with the former because of its implications for the latter.